2020
DOI: 10.1111/joim.13163
|View full text |Cite
|
Sign up to set email alerts
|

Use of the IL‐6R antagonist tocilizumab in hospitalized COVID‐19 patients

Abstract: Severely ill COVID‐19 patients have a high risk of admission to the intensive‐care unit (ICU) and requirement for mechanical ventilation (MV), with in‐hospital mortality reported as 18‐79% globally. 1‐4 . Among ICU patients in the United States (US), centers have reported 50% mortality. 5,6 Tocilizumab, an IL‐6 receptor (IL‐6R) antagonist, is FDA approved for the management of CAR T‐cell related Cytokine Release Syndrome (CRS) and may have utility in treatment of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 8 publications
0
23
0
Order By: Relevance
“…Indeed, clinical trials assessing the benefits of inflammatory cytokine blockade targeting IL-6 and its upstream mediator IL-1ß are in progress [9]. Given the heterogeneous preliminary results so far in trials applying IL-6 blockade in more severe cases of COVID-19 [22,23], the results of the present study may suggest to elucidate the specific role of IL-6 blockade in uncomplicated COVID-19 patients with cardiovascular comorbidities. Likewise, in light of the observed enhanced intravascular coagulation even during the uncomplicated phase of COVID-19 in patients with cardiovascular comorbidities, more aggressive anticoagulation treatment strategies may be warranted in these patients, as suggested in a recent retrospective analysis [24].…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, clinical trials assessing the benefits of inflammatory cytokine blockade targeting IL-6 and its upstream mediator IL-1ß are in progress [9]. Given the heterogeneous preliminary results so far in trials applying IL-6 blockade in more severe cases of COVID-19 [22,23], the results of the present study may suggest to elucidate the specific role of IL-6 blockade in uncomplicated COVID-19 patients with cardiovascular comorbidities. Likewise, in light of the observed enhanced intravascular coagulation even during the uncomplicated phase of COVID-19 in patients with cardiovascular comorbidities, more aggressive anticoagulation treatment strategies may be warranted in these patients, as suggested in a recent retrospective analysis [24].…”
Section: Discussionmentioning
confidence: 88%
“…All these studies assessed the effect of tocilizumab administration in patients with severe and/or critical COVID-19. Patel et al [ 40 ] reported the clinical outcomes of the two groups of severe and critical COVID-19 patients separately. Therefore, we have considered them as two separate studies.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 18 non-randomized articles reported the use of IL-6 inhibitor and its comparator for COVID-19, 16 studies using tocilizumab [ [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , 27 ], 1 using sarilumab [ 25 ], and 1 using siltuximab [ 26 ]. The therapeutic interventions, drug dosing, IL-6 markers, and clinical outcomes are presented in Table 2 .…”
Section: Resultsmentioning
confidence: 99%